Educational Philosophy: Reflections on the Teacher's Personality in the Story of the Prophet Ibrahim AS in the Qur'an - Aristanti, Suci; Nursalim, Mochamad; Masitoh, Siti (Continuous Education: Journal of Science and Research, 2023)
Teacher personality is one side that always be in the spotlight, teachers become good role model for students or for society. Teachers should be able to keep themselves by maintaining their professionalism safely, wisely, so that people and learners are easier to imitate teachers who have a whole personality and not a split personality. The researcher studied the stories in the Qur'an about the stories of the prophet Ibrahim AS as well as relating to existing educational theories. Researcher argued that it would be good if trying to find the profile of teacher personality in the Qur'an, because with the historical approach can learn everything that had ever happened as ibrah and the examples for teachers in the present day. The story of the research sample was the stories of the prophet Ibrahim As that was contained in the Qur'an. This research included library research because researcher tried to find the personality of the prophet Ibrahim in the Qur'an using content analysis. Researcher examined by using books of Quranic interpretation and then related it to theories of teacher personality, then drawing conclusion. The teacher personality profiles can conclude from the stories of the prophet Ibrahim in the Qur'an: (a) steadiness and personal integrity, (b) Alternatives thinking, (c) creative, (d) courageous, (e) honest, (f) rational and logical (g) friendly, opened and humble (h) Patience and sincere. (i) Responsibility.